Pinch analysis for the planning of power generation sector in the United Arab Emirates: A climate-energy-water nexus study - Lim, Xiao Y. (Animo Repository, 2018)
The United Arab Emirates has recently announced its 2050 Energy Plan, which aims for a 50% clean energy supply. The plan requires diversifying the nation's energy mix and adoption of more renewable energy sources. In addition, climate change and water scarcity issues are key factors to consider towards building an environmentally sustainable future in the country. Therefore, this paper uses Pinch Analysis to examine the 2050 target, focusing in three key aspects (i.e., carbon emissions, energy return on investment, and water footprint) of the country's power sector. Different scenarios for achieving the 2050 target are studied, accounting for demand growth, energy resource availability, and finally technology feasibility and cost projections. This approach provides a holistic assessment of the impact of each of the three aspects on the power generation sector. By constraining United Arab Emirates carbon emissions to 2012 levels, with maximum energy return on investment and minimum water footprint, the electricity sector in 2050 will be dominated by renewable energy, and particularly solar power. Furthermore, the interdependencies of energy and water policy issues are discussed. © 2018 Elsevier Ltd